Evidence-Based Medicine : How to practice and teach it. - Straus, Sharon E. (Edinburgh : Elsevier Churchill Livingstone, 2011)
This manual on practising and teaching evidence-based medicine shifts the focus from theory and explanation to tactics and clinical applications. The accompanying CD-ROM contains clinical examples, critical appraisals and background papers.
Previous ed.: Edinburgh: Churchill Livingstone, 2005.
CD-ROM and cards in pockets attached to inside front and back covers.
Includes bibliographical references and index.
Keywords: Evidence-based medicine